2014
DOI: 10.1103/physrevd.89.084063
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties of astrophysical gravitational-wave backgrounds

Abstract: We investigate how a stochastic gravitational-wave background, produced from a discrete set of astrophysical sources, differs from an idealized model consisting of an isotropic, unpolarized, and Gaussian background. We focus, in particular, on the different signatures produced from these two cases, as observed in a cross-correlation search. We show that averaged over many realizations of an astrophysical background, the cross-correlation measurement of an astrophysical background is identical to that of an ide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Another promising detection method that has been tested in the context of the ET Mock Data Challenge ) for the population of NSNS is to examine the residual of the null stream, which contains no GW signal and arises from the sum of the three ET detectors. However, Meacher et al (2014) has shown that non-Gaussian backgrounds can be detected with no loss of sensitivity by the standard crosscorrelation statistic used for Gaussian backgrounds as long as there is a strong enough signal present in the observation time, even if they do not overlap. This results was verified by the standard cross-correlation used in the Einstein Telescope Mock Data Challenges .…”
Section: Resultsmentioning
confidence: 99%
“…Another promising detection method that has been tested in the context of the ET Mock Data Challenge ) for the population of NSNS is to examine the residual of the null stream, which contains no GW signal and arises from the sum of the three ET detectors. However, Meacher et al (2014) has shown that non-Gaussian backgrounds can be detected with no loss of sensitivity by the standard crosscorrelation statistic used for Gaussian backgrounds as long as there is a strong enough signal present in the observation time, even if they do not overlap. This results was verified by the standard cross-correlation used in the Einstein Telescope Mock Data Challenges .…”
Section: Resultsmentioning
confidence: 99%
“…These fluctuations are much smaller than the current local merger uncertainty [44]. The predictions may also be conservative.…”
mentioning
confidence: 84%
“…While Eq. (4) is derived by assuming a Gaussian background [6], it can also be applied to non-Gaussian backgrounds (with signals that are clearly separated in time) such as the binary black hole background considered here [44]. The different black curves shown in this plot illustrate the improvement in expected sensitivity in the coming years.…”
mentioning
confidence: 99%
“…Given the recent observations of binary black hole mergers GW150914 and GW151226 [6,7], we expect the SGWB to be nearly isotropic [8] and dominated [9] by compact binary coalescences [10][11][12]. The LIGO and Virgo Collaborations have pursued the search for an isotropic stochastic background from LIGO's first observational run [13].…”
Section: Directional Limits On Persistent Gravitational Waves From Admentioning
confidence: 99%